(untitled) (American Journal of Research in Humanities and Social Sciences, 2026)
This article analyzes the construction history, architectural features, and place of the Sayid Atalyk madrasah in Denau – one of the ancient cities of the Surkhandarya oasis – within the architecture of the Denau bekdom.